In silico prediction for the investigation of comedication interferences in quantitative LC–MS detection in the SRM mode. (August 2012) - Bruderer, Tobias; Varesio, Emmanuel; Winter, Serge; Hopfgartner, Gérard
Background: LC–SRM/MS method validation in quantitative bioanalysis requires screening for potential interferences caused by the coelution of comedications or their metabolites. Current approaches are time-consuming, difficult to transfer to other experimental systems and not comprehensive. We propose an in silico strategy based on predicted LC retention time and MS precursor interferences to rank compounds that could potentially interfere with the analyte of interest, followed by a more focused experimental verification.Results: The suggested screening strategy was applied to investigate 129 potential comedications in everolimus patient samples analyzed with a validated LC–SRM/MS assay. A mixture of analytes with the same nominal mass was also investigated to illustrate the interference issues in SRM method development.Conclusion: A strategy was developed that allows the rapid screening of comedications, which is scalable to any analyte and transferable to any other LC–MS system.